Computer desktop encyclopedia - Freedman, Alan (AMACOM, 1999)
"The Computer Desktop Encyclopedia, Second Edition contains completely updated Internet and World Wide Web terms, new telecommunications technologies and vendors, even a TCP/IP micro-lesson. Outstanding in its coverage, The Encyclopedia includes more than 1,000 pages of clear, concise definitions and explanations of everything you need to know about computers." "Packed with graphics (more than 750 illustrations altogether) and tutorials, it will appeal to anyone who wants a deeper understanding of all things computer. And, best of all, it comes with a CD-ROM version (complete with Windows help and "how to" entries) so you can keep The Encyclopedia on your computer desktop as well as your bookshelf."--BOOK JACKET.